HIV‐free survival at 12–24 months in breastfed infants of HIV‐infected women on antiretroviral treatment. Issue 7 (24th May 2016) - Chikhungu, Lana Clara; Bispo, Stephanie; Rollins, Nigel; Siegfried, Nandi; Newell, Marie‐Louise
Abstract: Objective: To provide estimates of HIV‐free survival at 12–24 months in breastfed children by maternal ART (6 months or lifelong) to inform WHO HIV and Infant Feeding guidelines. Methods: Eighteen studies published 2005–2015 were included in a systematic literature review (1295 papers identified, 156 abstracts screened, 55 full texts); papers were analysed by narrative synthesis and meta‐analysis of HIV‐free survival by maternal ART regimen in a random effects model. We also grouped studies by feeding modality. Study quality was assessed using a modified Newcastle–Ottawa Scale (NOS) and GRADE. Results: The pooled estimates for 12‐month HIV‐free survival were 89.8% (95% confidence interval, CI: 86.5%, 93.2%) for infants of mothers on ART for 6 months post‐natally (six studies) and 91.4% (95% CI 87.5%, 95.4%) for infants of mothers on lifelong ART (three studies). Eighteen‐month HIV‐free survival estimates were 89.0% (95% CI 83.9%, 94.2%) with 6 months ART (five studies) and 96.1% (95% CI 92.8%, 99.0%) with lifelong ART (three studies). Twenty‐four‐month HIV‐free survival for infants whose mothers were on ART to 6 months post‐natally (two studies) was 89.2% (95% CI 79.9%, 98.5%). Heterogeneity was considerable throughout. In four studies, HIV‐free survival in breastfed infants ranged from 87% (95% CI 78%, 92%) to 96% (95% CI 91%, 98%) and in formula‐fed infants from 67% (95% CI 35.5%, 87.9%) to 97.6% (95% CI 93.0%, 98.2%). Conclusion: Our results highlight the importance of breastfeeding for infant survival and of ART in reducing the risk of mother‐to‐child HIV transmission and support the WHO recommendation to initiate ART for life immediately after HIV diagnosis.